431 Evaluation of Project Bhasa, Bangladesh. (20th November 2022) - Wills, Steve; Hossain, Shafkat; Mecrow, Tom; Williams, Darren; Dutta, Notan; Parveen, Rehana; Jagnoor, Jagnoor; Rahman, Aminur
Abstract : Background: Over 14, 500 children drown in Bangladesh annually. The aim of Project Bhasa was to design, implement and evaluate community-based drowning prevention interventions targeting children aged 1 to 10 in the Barishal Division of Southern Bangladesh, an area known to have disproportionately high rates of drowning. Methods: A concurrent mixed methods study design was followed with outcome evaluated through a quasi-experimental design. A baseline survey was conducted in 2016 to understand the burden and context of drowning prior to intervention design, complemented by a qualitative study to provide an understanding of contributing factors. The core interventions were implemented between 2017 and 2019: day-care for children aged 1–5 years, survival swimming for children aged 6–10 years, and community first response. Community-based methods for implementation were adopted, including creation of village injury prevention committees. Both qualitative and quantitative monitoring data was used to explore the intervention fidelity. An endline survey was also conducted on conclusion of project activities, in both intervention and comparison areas. Analysis: The findings from the baseline and end-line results were promising, but inconclusive. Large reductions in both fatal and non-fatal drowning were observed in the intervention area, however we are unable to say with confidence that these reductions differed significantly to the comparison area. After three years of Project Bhasa, the fatal drowning rate in the intervention areas for children aged 1 to 10 years reduced by 53.7%, from 152.2 to 70.4 per 100, 000 population per year. In the comparison area, rates of fatal drowning in these age-groups reduced by 37.5%. Monitoring data suggests that children aged two years and under, who are most vulnerable to drowning, had difficulty accessing the day-care intervention due to cultural and practical challenges. Outcomes: Large reductions in fatal and non-fatal drownings were recorded in the both the intervention and comparison areas for children aged 1 to 10 years. Alternative methods to protect children under two years of age need to be carefully considered and tested. Learning Outcomes: A need to better understand the wider contextual determinants which may influence the reduction of drowning in the Barishal division.